2016
DOI: 10.1038/srep39428
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced Mixture of Antagonistic Pressures Promotes the Evolution of Parallel Movement

Abstract: A common hypothesis about the origins of collective behaviour suggests that animals might live and move in groups to increase their chances of surviving predator attacks. This hypothesis is supported by several studies that use computational models to simulate natural evolution. These studies, however, either tune an ad-hoc model to ‘reproduce’ collective behaviour, or concentrate on a single type of predation pressure, or infer the emergence of collective behaviour from an increase in prey density. In nature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…For example, instead of the attraction to the nearest neighbour 1 , reasonably complicated movement rules based on group densities and individual positions have been demonstrated as necessary for the emergence of large groups in two-dimensional space, the environment of most terrestrial animals 1317 . In consideration of the ultimate reasons, a growing number of simulations have demonstrated that under the selfish herd scenario, the evolution of prey agents’ movement strategies can result in stable states where selfish agents assemble large and dense groups 1822 . These theoretical studies indicate that from both proximate and ultimate aspects, the selfish herd scenario would emerge and persist during evolution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, instead of the attraction to the nearest neighbour 1 , reasonably complicated movement rules based on group densities and individual positions have been demonstrated as necessary for the emergence of large groups in two-dimensional space, the environment of most terrestrial animals 1317 . In consideration of the ultimate reasons, a growing number of simulations have demonstrated that under the selfish herd scenario, the evolution of prey agents’ movement strategies can result in stable states where selfish agents assemble large and dense groups 1822 . These theoretical studies indicate that from both proximate and ultimate aspects, the selfish herd scenario would emerge and persist during evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the specific impact of crowding effects on aggregating was less considered and examined in related works. For example, a prey agent in a selfish herd model was often treated as a (volume-less) point 1319 or assigned a constant speed 1822 , despite that limited mobility due to the physical embodiment of agents has been an important topic for swarm robotic algorithms 23,24 and human crowd simulations 25,26 . The simplifications in traditional selfish herd models may prevent their outputs from explaining real collective behaviours in more detail.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last couple of years, computer models have become an important tool for either studying the behaviour of animal groups and their evolution, or generating spectacular animations for use in computer games and movies . Roughly, computer models of collective behaviour can be classified into three groups—individual‐based models, flow‐based models, and hybrid models …”
Section: Introductionmentioning
confidence: 99%